Survey on the Knowledge Level and Attitudes of University Students About Human Papilloma Virus Infection and Vaccination and Assessing Healthy Living Behaviors - Tosun, Hale; GÜL, ASİYE; Yazıcı, Saadet (Springer Heidelberg, 2022)
Aim This study was carried out to determine the knowledge and attitude about human papillomavirus (HPV) infection and vaccination and healthy lifestyle behaviors of female university students. Subject and methods Students completed a form containing socio-demographic data and questions about HPV infection and vaccination and the Healthy Lifestyle Behaviors Scale-II (HLBS). For the analysis of the data, percentage, mean, standard deviation, T-test, and one-way ANOVA test were used in independent groups. Results The mean age of the female students was 19.53 +/- 1.57. Of the students, 74.7% (n = 470) had no knowledge about cervical cancer, 80.6% (n = 507) had no knowledge about HPV, and 1.7% (n = 11) had had the HPV vaccination. "Not know" to all the statements about HPV infection and vaccination is high in general. The total score of the HLBS was 126.43 +/- 17.70. The mean scores of the HLBS subgroup were the highest in the aspects of spiritual development and interpersonal relations. The HLBS total scores of those who know about the HPV vaccine were higher than those who do not know and those who have insufficient knowledge. Conclusion Knowledge of HPV infection and vaccination is important for young women. It is necessary to develop healthy lifestyle behaviors during university education.
Keywords: Healthy Lifestyle Behaviors; Human Papillomavirus Infection; Vaccination